Pemanfaatan Barang Milik Daerah Dalam Bentuk Perjanjian Bangun Guna Serah Gedung HI Tech Mall - Khoiruddin, Amir; Yudhantaka, Lintang (Legal Spirit, 2024)
The implementation of the utilization of State or Regional Property can be carried out through the Build, Operate, and Transfer Agreement with the hope that it can continue to strive to carry out regional development by collaborating with the private sector. Cooperation between the Surabaya City Government and private parties is certainly based on an agreement that binds both parties. This study aims to determine the realization of legal certainty over the use of Regional Property in the form of legal protection for third parties (HI Tech Mall Merchants). This research uses analytical descriptive methods and uses a qualitative approach. The results showed that the agreement implemented by the parties has guaranteed legal certainty and is binding on each other based on the suitability of the elements that must be contained in a text of agreement in civil law and the existence of preventive and repressive legal protection for traders who still occupy shop booths in the HI Tech Mall Building until now.